2022
DOI: 10.3390/life12070996
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities in Ventricular Conduction Following Treatment with Heptanol: A Multi-Electrode Array Study in Langendorff-Perfused Mouse Hearts

Abstract: Background: Previous studies have associated slowed ventricular conduction with the arrhythmogenesis mediated by the gap junction and sodium channel inhibitor heptanol in mouse hearts. However, they did not study the propagation patterns that might contribute to the arrhythmic substrate. This study used a multi-electrode array mapping technique to further investigate different conduction abnormalities in Langendorff-perfused mouse hearts exposed to 0.1 or 2 mM heptanol. Methods: Recordings were made from the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Furthermore, the conduction inhomogeneity index can be employed to differentiate between both types of abnormalities. 34 The findings of this study show that the absolute inhomogeneity and conduction inhomogeneity index change synchronously, demonstrating that the change in inhomogeneity after hypothermic global ischemia-reperfusion is primary. A study has observed that the rat hearts resumed sinus rhythm and conduction within 10 to 15 minutes after 60 minutes of arrests at room temperature.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, the conduction inhomogeneity index can be employed to differentiate between both types of abnormalities. 34 The findings of this study show that the absolute inhomogeneity and conduction inhomogeneity index change synchronously, demonstrating that the change in inhomogeneity after hypothermic global ischemia-reperfusion is primary. A study has observed that the rat hearts resumed sinus rhythm and conduction within 10 to 15 minutes after 60 minutes of arrests at room temperature.…”
Section: Discussionsupporting
confidence: 52%
“…Using mice anesthetized with 1.5% tribromoethanol (0.02 mL/g; WXBD3759V, Sigma, St. Louis, Missouri, USA), and supported by a tracheal intubation ventilator, mouse chests were surgically opened with full exposure to the heart. Following this, the pericardium was removed, epicardial conduction velocity (CV), absolute inhomogeneity and inhomogeneity index was recorded and analyzed using the Electrical Mapping System (EMS64-USB-1003, MappingLab, Oxford, UK) and EMapScope 4.0 (MappingLab, Oxford, UK), as detailed previously [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to all these indicators, the most widely employed measurement of heterogeneity is the Spatial Inhomogeneity index, described by Lammers in 1990 [21] . This metric, based on conduction delays across the tissue, has been applied to high-density multielectrode recordings to evaluate arrhythmogenicity [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%